Answer:
Solution given:
opposite:9
adjacent: 12
![\theta=?](https://tex.z-dn.net/?f=%5Ctheta%3D%3F)
Relationship between opposite and adjacent is given by tan angle
so
![Tan \theta=\frac{opposite} {adjacent}=\frac{9}{12}](https://tex.z-dn.net/?f=Tan%20%5Ctheta%3D%5Cfrac%7Bopposite%7D%20%7Badjacent%7D%3D%5Cfrac%7B9%7D%7B12%7D)
![Tan \theta=\frac{3}{4}](https://tex.z-dn.net/?f=Tan%20%5Ctheta%3D%5Cfrac%7B3%7D%7B4%7D)
![\theta=Tan^{-1}\frac{3}{4}](https://tex.z-dn.net/?f=%5Ctheta%3DTan%5E%7B-1%7D%5Cfrac%7B3%7D%7B4%7D)
![\bold{\theta=36.8°}](https://tex.z-dn.net/?f=%5Cbold%7B%5Ctheta%3D36.8%C2%B0%7D)
#11.
hypotenuse[h]=11cm
opposite/perpendicular[P]=b cm
adjacent/base[b]=a cm
now
![\theta=62°](https://tex.z-dn.net/?f=%5Ctheta%3D62%C2%B0)
Relationship between height and hypotenuse is given by Sin angle
:.
Sin 62°=![\frac{opposite}{hypotenuse}=\frac{b}{11}](https://tex.z-dn.net/?f=%5Cfrac%7Bopposite%7D%7Bhypotenuse%7D%3D%5Cfrac%7Bb%7D%7B11%7D)
doing crisscrossed multiplication
b=Sin 62°*11
:.b=9.71 cm
a) At <u>9</u><u>.</u><u>7</u><u>1</u><u> </u>cm height does the ladder touch the building.
again
Relationship between base and hypotenuse is given by Cos angle
:.Cos 62°=![\frac{base}{hypotenuse}=\frac{a}{11}](https://tex.z-dn.net/?f=%5Cfrac%7Bbase%7D%7Bhypotenuse%7D%3D%5Cfrac%7Ba%7D%7B11%7D)
doing crisscrossed multiplication
a=Cos 62°×11
a=5.16cm
b) the distance between the foot of the ladder and the building is <u>5.16cm.</u>
Answer:
true
Step-by-step explanation:
Answer:
a = 46
b = 20
c = 15
b+c ≤ a
20 + 15 ≤ 46
61 ≤ 46
Step-by-step explanation:
Answer:
Y= 2e^(5t)
Step-by-step explanation:
Taking Laplace of the given differential equation:
s^2+3s-10=0
s^2+5s-2s-10=0
s(s+5)-2(s+5) =0
(s-2) (s+5) =0
s=2, s=-5
Hence, the general solution will be:
Y=Ae^(-2t)+ Be^(5t)………………………………(D)
Put t = 0 in equation (D)
Y (0) =A+B
2 =A+B……………………………………… (i)
Now take derivative of (D) with respect to "t", we get:
Y=-2Ae^(-2t)+5Be^(5t) ....................... (E)
Put t = 0 in equation (E) we get:
Y’ (0) = -2A+5B
10 = -2A+5B ……………………………………(ii)
2(i) + (ii) =>
2A+2B=4 .....................(iii)
-2A+5B=10 .................(iv)
Solving (iii) and (iv)
7B=14
B=2
Now put B=2 in (i)
A=2-2
A=0
By putting the values of A and B in equation (D)
Y= 2e^(5t)
4.6x^2+3.2-4x+2.7x^2-x=4.6x^2+3.2x+-4x+2.7x^2+-xCombine like terms:4.6x^2+3.2x+-4x+2.7x^2+-x=(4.6x^2+2.7x^2)+(3.2x+-4x+-x)=7.3x^2+-1.8xAnswer:7.3x^2-1.8x